2014
DOI: 10.1007/s00299-014-1605-8
|View full text |Cite
|
Sign up to set email alerts
|

A simple and reliable multi-gene transformation method for switchgrass

Abstract: A simple and reliable Agrobacterium -mediated transformation method was developed for switchgrass. Using this method, many transgenic plants carrying multiple genes-of-interest could be produced without untransformed escape. Switchgrass (Panicum virgatum L.) is a promising biomass crop for bioenergy. To obtain transgenic switchgrass plants carrying a multi-gene trait in a simple manner, an Agrobacterium-mediated transformation method was established by constructing a Gateway-based binary vector, optimizing tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…In fact, we have successfully obtained transgenic switchgrass plants from 18-monthold calli (Ogawa et al 2014). These findings indicate that caryopsis-derived Type I callus is useful source for genetic transformation of switchgrass.…”
mentioning
confidence: 99%
“…In fact, we have successfully obtained transgenic switchgrass plants from 18-monthold calli (Ogawa et al 2014). These findings indicate that caryopsis-derived Type I callus is useful source for genetic transformation of switchgrass.…”
mentioning
confidence: 99%
“…In this study, 24 explants out of 100 survived on the bialaphos containing selection medium and were successfully transformed grapevine clones. This limited number of successfully transformed grapevine clones is not uncommon and has been attributed by various researchers to several different factor that influence the relative low transformation efficiency including initial difficulties experienced in the introduction of foreign genes and the selection and regeneration of transformed cells in grape species (Perl and Eshdat, 1998), escape genes during selection (Ogawa et al, 2014), problems in the production of roots increasing the time to get plantlets (Luth and Moore, 1999), trouble in conditions required for successful Agrobacterium infection, and also identifying the suitable Agrobacterium strain and selectable marker gene (Carimi et al, 2012). Several methods for genetic transformation have been attempted for grape, but only Agrobacterium mediated transformation has been previously successful (Vivier and Pretorius, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Six-to twelve-month-old caryopsis-derived Type I calli were transformed using the Agrobacterium-mediated method of Ogawa et al (2014) with modifications. One callus line of cultivar ' Alamo' , A09-01, was used for optimization of transformation conditions.…”
Section: Agrobacterium-mediated Transformationmentioning
confidence: 99%
“…We previously found that the transformation efficiency of caryopsis-derived Type I calli could be increased by prolonged cocultivation (Ogawa et al 2014). In the present study, we aimed to establish a simple and highly efficient Agrobacterium-mediated transformation method using caryopsis-derived Type I calli of switchgrass by focusing on the cocultivation conditions as well as the preculture conditions.…”
mentioning
confidence: 97%
See 1 more Smart Citation